Desain Optimalisasi dan Penjadwalan Produksi Penambangan Batubara Pada Pit Granit Extend Seam 6 PT. Cipta Bersama Sukses Desa Beji Mulyo Provinsi Sumatera Selatan - Ravilqi Medri; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2023)
PT. Cipta Bersama Sukses has two Granit Extend pit mining locations: seam 5 and seam 6. On August 8, 2022, an avalanche occurred which covered the seam 5 mining area so that coal-getting activities or coal production could not be continued. because this condition was considered unsafe and inefficient. Then the mining plan changed to the seam 6 area, So it is necessary to design the optimization of the seam 6 area, design the coal getting for September and October 2022, as well as production scheduling so that mining activities are well planned. Based on the optimization design in August 2022, the seam 6 area obtained 43.248,117 tons of coal and 304.293 bcm of overburden, and the pit design in September 2022 obtainedan  overburden of 306.198 bcm overburden and 93.017,183 tons of coal, while in October 2022, overburden was obtained of 323.053 bcm and 102.160,480 tons of coal. To achieve the production target, production planning is required which aims to calculate unit requirements for mining activities. Based on the analysis, the number of fleets needed for overburden removal activities is 6 fleets consisting of 3 fleets with 4 DT units each, 1 fleet with 2 ADT units and 2 fleets with 3 DT units each. The amount of overburden production is 310,380.66 bcm Whereas for coal-getting activities, 1 fleet consisting of 3 DT units is needed with a total production of 47.178,60 tons.